Comparative analysis of the specifics of a compliment in Chinese, English and Kazakh speech culture (Journal of Oriental Studies, 2017)
The article considers a compliment as a speech act in terms of its objectand purpose, depending on the gender of the Chinese, English andKazakh lingvoculture also considered a compliment design principles, theprinciples of its formality, used language means.